2011
DOI: 10.1021/jo200897q
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Azaheterocycles from Aryl Ketone O-Acetyl Oximes and Internal Alkynes by Cu–Rh Bimetallic Relay Catalysts

Abstract: A synthetic method for azaheterocycles from aryl ketone O-acetyl oximes and internal alkynes has been developed by using the Cu(OAc)(2)-[Cp*RhCl(2)](2) bimetallic catalytic system. The reactions proceeded with both of anti- and syn-isomers of oximes with a wide scope of substituents. The Cu-Rh bimetallic system could be applied for the synthesis of isoquinolines as well as β-carboline, furo[2.3-c]pyridine, pyrrolo[2,3-c]pyridine, and thieno[2,3-c]pyridine derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(51 citation statements)
references
References 74 publications
(31 reference statements)
1
50
0
Order By: Relevance
“…It was also observed that, oxime selectivity increases with temperature. As we increased temperature from room temperature (30 °C) to 50 °C oxime selectivity was also increased from 53% to 90% (Table 2 entries [10][11][12]. Further rise in the temperature does not show any influence on the oxime selectivity ( Table 2, entry 13).…”
Section: Resultsmentioning
confidence: 94%
“…It was also observed that, oxime selectivity increases with temperature. As we increased temperature from room temperature (30 °C) to 50 °C oxime selectivity was also increased from 53% to 90% (Table 2 entries [10][11][12]. Further rise in the temperature does not show any influence on the oxime selectivity ( Table 2, entry 13).…”
Section: Resultsmentioning
confidence: 94%
“…First, condensation of benzothiophene-6-carbaldehyde 3 ha with p-anisidine was followed by rhodium(III)-catalyzed, aldimine-directed oxidative annulation with diphenylacetylene [20] to afford, upon hydrolysis, 7H-indeno [5,6-b]thiophen-7-one 8 (Scheme 7 a). Second, O-acetyloxime 9 derived from 6-acetylbenzothiophene 3 ia was subjected to rhodium(III)catalyzed redox-neutral annulation with diphenylacetylene [21] to afford thieno[3,2-g]isoquinoline 10 (Scheme 7 b). Finally, imine 11 derived from 6-aminobenzothiophene 3 oa and acetophenone participated in a palladium-catalyzed dehydrogenative cyclization reaction [22] to afford 7H-thieno[3,2f]indole 12.…”
Section: Methodsmentioning
confidence: 99%
“…[2,3] Despite substantial progress in the field, the development of highly atom-economic, sustainable routes that can achieve CÀ H functionalization under external-oxidizing-reagent-free conditions that release nontoxic waste products (e. g., H 2 O) remains a challenging area. [3][4][5][6] While the annulation of aromatic oximes with internal alkynes has been thoroughly investigated for the preparation of 3,4-disubstituted isoquinolines (Scheme 1a-i), [3,5] similar versions with alkenes are rare. [3][4][5][6] While the annulation of aromatic oximes with internal alkynes has been thoroughly investigated for the preparation of 3,4-disubstituted isoquinolines (Scheme 1a-i), [3,5] similar versions with alkenes are rare.…”
mentioning
confidence: 99%
“…[4] In recent years, transition-metalcatalysed intermolecular annulation of aromatic oximes and their derivatives (often esters) with unsaturated hydrocarbons (e. g., alkynes, allenes, alkenes, ketenes) have proved to be promising platforms for the preparation of nitrogen-containing heterocycles, wherein the N À O bond in aromatic oximes serves as the internal oxidative chelation group to selectively achieve ortho-C(sp 2 )À H functionalization. [3][4][5][6] While the annulation of aromatic oximes with internal alkynes has been thoroughly investigated for the preparation of 3,4-disubstituted isoquinolines (Scheme 1a-i), [3,5] similar versions with alkenes are rare. [6] Moreover, these transformations focus on special alkenes, including vinyl acetates, [6a] 1,3-dienes [6b] and electron-poor alkenes, [6c] which serve as convenient acetylene equivalents for the synthesis of 3-substituted isoquinolines.…”
mentioning
confidence: 99%
See 1 more Smart Citation